Epidemiology and clinic of microbial-inflammatory nephropathy in children living in an ecologically unfavorable region - E. P. Sitnikova; T. G. Pukhova; E. M. Spivak (LLC "Diagnostics and Vaccines", 2022)
The aim is to establish the epidemiology and features of the clinic of microbial inflammatory nephropathy in children living in an ecologically unfavorable area.Research methods. The prevalence of microbial-inflammatory nephropathies and their incidence in the urban children's population, as well as in areas with favorable and unfavorable environmental situation were analyzed. A clinical and laboratory examination of patients was carried out with an assessment of the features of the manifestations of the disease in children living in an area with environmental pollution.The results of the study. Over the past two decades, there has been a decrease in the incidence of microbial inflammatory nephropathies and their general prevalence in the urban children's population. However, in an urban area with an unfavorable environmental situation, a significant increase in these epidemiological indicators has been recorded over a ten-year period. The peculiarities of microbial-inflammatory nephropathies in children living in an area with significant air and soil pollution are their occurrence against the background of congenital anomalies or malformations of the kidneys and urinary tract, frequent relapses, the presence of complications. They are characterized by a frequent combination of kidney and bladder lesions, higher activity of the inflammatory process with impaired renal function, slow reverse dynamics of symptoms during treatment.Conclusion. Microbial-inflammatory nephropathies in children living in ecologically unfavorable areas of the city have features of epidemiology and clinical manifestations, which must be taken into account when carrying out medical support for this category of patients.